Antepartum stillbirth rates during the COVID‐19 pandemic in Austria: A population‐based study. Issue 3 (31st October 2021) - Muin, Dana A.; Neururer, Sabrina; Falcone, Veronica; Windsperger, Karin; Helmer, Hanns; Leitner, Hermann; Kiss, Herbert; Farr, Alex
Abstract: Background: The coronavirus disease 2019 (COVID‐19) pandemic caused by severe acute respiratory syndrome coronavirus 2 has had dramatic effects on the pregnant population worldwide, increasing the risk of adverse perinatal outcomes. Objective: To assess the incidence of antepartum stillbirth (aSB) during the COVID‐19 pandemic in Austria. Methods: We collected epidemiological data from the Austrian Birth Registry and compared the rate of aSB (i.e., fetal death at or after 24 +0 gestational weeks) during the pandemic period (March–December 2020) and in the respective pre‐pandemic months (2015–2019). Results: In total, 65 660 pregnancies were included, of which 171 resulted in aSB at 33.7 ± 4.8 gestational weeks. During the pandemic, the aSB rate increased from 2.49‰ to 2.60‰ ( P = 0.601), in contrast to the significant decline in preterm deliveries at or before 37 gestational weeks from 0.61‰ to 0.56‰ (relative risk [RR] 0.93; 95% confidence interval [CI] 0.91–0.96; P < 0.001). During the first lockdown, the aSB rate significantly increased from 2.38‰ to 3.52‰ ( P = 0.021), yielding an adjusted odds ratio of 1.57 (95% CI 1.08–2.27; P = 0.018). The event of aSB during the COVID‐19 pandemic was strongly related with increased fetal weight and maternal obesity. Conclusion: In Austria, there has been an overall increase in the incidence of aSB during the pandemic with a significant peak during the first lockdown. Abstract : During the COVID‐19 pandemic, particularly during the first lockdown, antepartum stillbirth rate in Austria increased by 11.4 cases per 100 live births.